Retinal blood vessel segmentation by a MAS approach - Pereira, Carla (2013)
Retinal blood vessels segmentation by color fundus images analysis has got huge importance for the diabetic retinopathy early diagnosis. Several interesting computational approaches have been done in this field, but none of them has shown the required performance due to the use of global approaches. Therefore, a new approach is proposed based on an organization of agents enabling vessels detection. This multi-agent approach is preceded by a preprocessing phase in which the fundamental filter is a Kirsch derivative improved version. This first phase allows an environment construction where the agents are situated and interact. Then, blood vessels segmentation emerges from agents’ interaction. According to this study, competitive results were achieved comparing to those found in the present literature. It seems to be that a very efficient system for the diabetic retinopathy diagnosis can be built using MAS mechanisms.